Facemask wearing does not impact neuro-electrical brain activity - Ahmad Tamimi; Said Dahbour; Assma Al-Btush; Abdelkarim Al-Qudah; Amira Masri; Subhi Al-Ghanem; Malik E. Juweid; Yazan Olaimat; Amer Al Qaisi; Qutada Al-Soub; Maha Naim; Ali Sawalmeh; et al. (Scientific Reports, 2022)
Abstract Given the massive use of facemasks (FMs) during the covid-19 pandemic, concerns have been raised regarding the effect of FMs wearing on overall health. This study aimed at evaluating the effect of surgical FM on brain neuro-electrical activity. Electroencephalography (EEG) background frequency (BGF) and background amplitude (BGA) was performed on 30 volunteers before (baseline), during and after wearing a FM for 60 min. Measurements were done during normal ventilation, hyperventilation and post-hyperventilation (PHVR). Blood gas levels were assessed at baseline and after FM use. EEG analysis concerning baseline (without FM) (BGA), was 47.69 ± 18.60 µV, wearing FM, BGA was 48.45 ± 17.79 µV, post FM use BGA was 48.08 ± 18.30 µV. There were no statistically significant differences between baseline BGA and BGA under FM and post FM. BGF, Baseline data were 10.27 ± 0.79, FM use 10.30 ± 0.76 and post FM use was 10.33 ± 0.76. There were no statistically significant differences between baseline BGF and BGF under FM and post FM. Venous blood gases, and peripheral oxygen saturation were not significantly affected by FM use. Short-term use of FM in young healthy individuals has no significant alteration impact on brain's neuro-electrical activity